The rum diary [videorecording (DVD)] - Robinson, Bruce, 1946-; Depp, Johnny; Ribisi, Giovanni, 1974-; Eckhart, Aaron; Heard, Amber, 1986-; Thompson, Hunter S. (Sony Pictures Home Entertainment, 2011)
Tired of the noise and madness of New York, journalist Paul Kemp moves to Puerto Rico to write for a local newspaper. Adopting the rum-soaked life of the island, Kemp becomes obsessed with the fiancee of Sanderson, a businessman involved in shady property development deals. When he is recruited by Sanderson to write favorably about his latest unsavory scheme, Kemp is presented with the choice to use his words for the corrupt businessman's financial benefit, or use them to take him down.